Emergence of immune-related adverse events correlates with pathological complete response in patients receiving pembrolizumab for early triple-negative breast cancer - Maximilian Marhold; Simon Udovica; Anna Halstead; Mona Hirdler; Muna Ferner; Kerstin Wimmer; Zsuzsanna Bago-Horvath; Ruth Exner; Florian Fitzal; Kathrin Strasser-Weippl; Tim Robinson; Rupert Bartsch (OncoImmunology)
Based upon results of the KEYNOTE-522 trial and following approval by regulatory authorities, the addition of pembrolizumab to chemotherapy is now the standard-of-care for the treatment of early triple-negative breast cancer (eTNBC) (Clinical stage II-III). Pembrolizumab is a programmed cell death protein 1 monoclonal antibody, known to cause immune-related adverse events (irAEs) in a significant subset of patients. Real-world data on incidence, type and treatment strategies of irAEs in the setting of eTNBC treatment are sparse. In this multicenterretrospective analysis, we characterized real-world incidence of irAEs and treatment outcomes such as pathological complete response (pCR) from the combination of pembrolizumab and chemotherapy as neoadjuvant treatment for eTNBC.We found a rate of irAEs of all grades of 63.9% and of 20% for irAEs of grade 3 or higher. In the overall population, a pCR rate of 57.1% was observed. The emergence of irAEs correlated significantly with pCR (72.2% versus 30.8%; p =.03). Discontinuation of neoadjuvant chemotherapy before week 12 correlated significantly with a lower pCR rate.To our knowledge, this is the first study evaluating the real-world efficacy and safety of a neoadjuvant combination of chemotherapy and pembrolizumab in eTNBC, demonstrating a significant correlation between irAEs and pCR. Early discontinuation of neoadjuvant therapy due to AEs resulted in a lower pCR rate.